2003
DOI: 10.1243/147509003322596059
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate compressive strength of plate elements with pit corrosion wastage

Abstract: The aim of the present paper is to investigate the ultimate strength characteristics of plate elements with pit corrosion wastage under axial compressive loads. Collapse tests on a box column type of steel-plated structures with diOEerent degrees of pit corrosion damage are undertaken. A series of ANSYS non-linear nite element analyses for steel plate elements under axial compressive loads are carried out, varying the degree of pit corrosion intensity and plate geometric properties. In this paper, a new parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…It was observed that the ultimate strength of a pitted plate under edge shear is governed by the DOP. In contrast, it has been realized that the ultimate strength of a plate element under axial compressive loads is governed by the smallest cross-sectional area, i.e., the most corroded section of the plate [8].…”
Section: Ultimate Shear Strength Of Steel Plates With Pit Corrosion: mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the ultimate strength of a pitted plate under edge shear is governed by the DOP. In contrast, it has been realized that the ultimate strength of a plate element under axial compressive loads is governed by the smallest cross-sectional area, i.e., the most corroded section of the plate [8].…”
Section: Ultimate Shear Strength Of Steel Plates With Pit Corrosion: mentioning
confidence: 99%
“…Most recently, the authors [8] studied the ultimate strength characteristics of pitted plate elements under axial compressive loads and derived closed-form formulae for predicting the ultimate compressive strength of pitted plates.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, corrosion wastage, in conjunction with mechanical damage, is known to significantly contribute to age-related structural degradation of ship hulls [1]. Pitting corrosion, which is a localized form of corrosion, is known to be one of its most insidious form in terms of causing structural degradation and ultimately failure [2], and has attracted the attention of a number of researchers in recent years [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] among others. Mateus and Witz [6] investigated the effect of general corrosion on the post-buckling of plates using the uniform thickness reduction approach and a quasi-random thickness surface model.…”
Section: Introductionmentioning
confidence: 99%
“…Paik et al [8,9] studied the ultimate strength characteristics of pitted plate elements under axial compressive loads and in-plane shear loads, and derived closedform formulae for predicting the ultimate strength of pitted plates using the strength reduction (knock-down) factor approach. They dealt with the case where the shape of corrosion pits is a cylinder.…”
Section: Introductionmentioning
confidence: 99%